Implementation of Organizational Citizenship Behavior (OCB) and Emotional Exhaustion: Analysis of Leadership and Self Efficacy in Private Employees in the City of Padang - Menhard Menhard; Chintya Ones Charli; Rahmadani Hidayat; Ariyanto Masnum; Budi Hartoyo (Dinasti International Journal of Management Science, 2023)
This study aims to analyze the role of emotional exhaustion on Organizational Citizenship Behaviour (OCB) with leadership and self efficacy as independent variables. The population in this study was private employees in the city of Padang. To determine the sample, the use of Maximum Likelihood estimate is used which requires a total sample of 100-200 samples, the researcher will take a sample of 100-200 private employees in the city of Padang. The analysis method used is Analysis on SEM-PLS. The results of this study show that there is a significant influence of each variable of Leadership and self Efficacy on Emotional Fatigue, a significant influence of Leadership and self Efficacy on Organizational Citizenship Behaviour (OCB). This research model uses 4 variables and applies the concept of intervening. Where in this study analyzed with SEM-PLS. This research proves that leadership and self efficacy affect Organizational Citizenship Behaviour (OCB) with emotional fatigue as an intervening variable.